2022
DOI: 10.1002/biof.1925
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac troponins: Mechanisms of release and role in healthy and diseased subjects

Abstract: The cardiac troponins (cTns), cardiac troponin C (cTnC), cTnT, and cTnI are key elements of myocardial apparatus, fixed as protein complex on the thin filament of sarcomere and are involved in the regulation of excitationcontraction coupling of cardiomyocytes in the presence of Ca 2+ . Circulating cTnT and cTnI (cTns) increase following cardiac tissue necrosis, and they are consolidated biomarkers of acute myocardial infarction (AMI). However, the use of high sensitivity (hs)-immunoassay tests for cTnT and cTn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 113 publications
0
0
0
Order By: Relevance
“…34 A sustained increase in cTnI of less than 20% is considered characteristic of chronic myocardial injury, such as chronic kidney disease, diabetes, significant left ventricular hypertrophy, chronic heart failure and other diseases resulting in secondary chronic myocardial injury. 35 Although renal function can affect the clarity of cTnI, the main mechanism of its elevation is still caused by myocardial injury. 36 Domestic research shows that the serum cTnT level is positively correlated with LVMI.…”
Section: Discussionmentioning
confidence: 99%
“…34 A sustained increase in cTnI of less than 20% is considered characteristic of chronic myocardial injury, such as chronic kidney disease, diabetes, significant left ventricular hypertrophy, chronic heart failure and other diseases resulting in secondary chronic myocardial injury. 35 Although renal function can affect the clarity of cTnI, the main mechanism of its elevation is still caused by myocardial injury. 36 Domestic research shows that the serum cTnT level is positively correlated with LVMI.…”
Section: Discussionmentioning
confidence: 99%
“…Initially, it was thought that cTn could only be released following overt cellular necrosis; however, recently it has been suggested that release can occur in ischemia without necrosis [3]. A review of the subject by Ragusa and colleagues suggest release mechanisms, including apoptosis, necroptosis, physiological cardiomyocyte renewal, and cellular wounding can contribute to cTn release as well as necrosis [4]. An immunohistochemical study using a canine model of coronary occlusion ranging from 30 minutes to 6 hours demonstrated variable loss of both cTnT and cTnI in paraffin-embedded left ventricular myocardial sections [5].…”
Section: Clinical Utility Of Cardiac Troponin In Myocardial Damagementioning
confidence: 99%